Content analysis of Bukhar Zhyrau’s poetry in the context of religious-philosophical paradigm (Eurasian Journal of Religious Studies, 2023)
Kazakh zhyrau poets have a special socio-political, religious-ideological place in humanitarian science. Especially noticeable in the work of Bukhar Zhyrau, who in the XVIII century was a political figure and a batyr fought against the Dzungarian invasion. Bukhar Zhyrau’s works clearly show his deep knowledge of Islam and nomadic civilization, which stood on crossroads of colonial policy of Russian Empire. His works singing the Creator in different hypostases (Allah, Kudai, Tanir) revealed the peculiarities of social system of Kazakhs. Following from this, the relevance of chosen topic can be said clearly, as Kazakh traditional Islam is not yet fully studied and requires a special approach. Therefore, object of study was chosen Bukhar Zhyrau poetry, where he reveals features and differences of Kazakhs traditional Islam, as well as the philosophy of the time. The historical-cultural and religious studies approach of analyzing Bukhar Zhyrau’s works revealed his subtle empathy for the fate of Kazakhs. Thus, article aims study the religious-philosophical paradigms of Bukhar Zhyrau’s work by means research method content analysis. Main tasks of achieving the designated goal the actual problems of analyzing the content Bukhar Zhyrau’s poetry and structure composition. Historiographical review and Bukhar Zhyrau’s poetry acted as the main sources.
Keywords: Bukhar Zhyrau; poetry; traditional Islam; religion; philosophy; Kazakh society